The Mathematics Ethnic Learning Program in Improving the Understanding of Mathematical Concepts and the Character of Homeland Love: - - Wibowo, Sigit; Unik Ambarwati; Fery Muhamad Firdaus (International Journal of Elementary Education, 2023)
Mathematics learning is still considered abstract and challenging to understand for most elementary school students. This results in students' low understanding of mathematical concepts. This research aims to measure the effectiveness of the "Mathematics Ethnic Learning" program, which has been implemented to increase elementary school students' understanding of mathematical concepts and patriotism. This research uses a quantitative type of research with a one-group pretest-posttest research design and a quasi-experimental method. The sampling technique used is the purposive sampling technique. Data was obtained from a test for understanding mathematical concepts and the results of a Love of the Country character questionnaire. Data analysis used the paired sample t-test and n-gain test. This research shows that students' comprehension test scores and the love of the country character questionnaire before and after the program was implemented showed a significant increase in these two aspects. Based on the statistical analysis that has been carried out, it shows that learning mathematics by applying traditional games can significantly influence students' understanding of the concept and character of patriotism. Furthermore, after being tested using the n-gain score formula, it showed that traditional games were quite effective in increasing understanding of mathematical concepts and the character of loving one's country. It was concluded that Mathematics Ethnic Learning can increase elementary school students' understanding of mathematical concepts and their sense of patriotism.